HUBUNGAN KERJASAMA INDONESIA DENGAN AMERIKA SERIKAT DALAM PENINGKATAN KUALITAS UDARA DAN KESEHATAN PUBLIK JAKARTA - Mayasari, Onita; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to analyze the cooperation between the Jakarta administrationand the Government of the United States United States Environmental ProtectionAgency (U.S. EPA) in improving air quality and public health in Jakarta. Air pollutionin the city has increased from year to year. This is due to the rapid development of thearea in Jakarta from the sectors of population, transportation, and industry. While theUnited States Environmental Protection Agency (U.S. EPA) offers cooperation to thegovernment of DKI Jakarta in improving air quality and public health in Jakarta.The author analyzes the case using descriptive qualitative analytical methods tofind data and facts through some literature such as books, journals, and websites. Thetheory is used to analyze the cooperation between Jakarta administration by the UnitedStates Environmental Protection Agency (U.S. EPA) in improving air quality and publichealth in Jakarta is the perspective of international cooperation by KJ Holsti and GreenThought theory.These results explained that the cooperation between Indonesia and the UnitedStates in the improvement of air quality in Jakarta Breath Easy program consists of sixphases but only three phases which have been running. However, cooperation betweenIndonesia and the United States in the improvement of air quality Jakarta has given theresults of the air in Jakarta where conditions began to improve.Keywords: Air Pollution, International Cooperation, Program Breath Easy, Jakarta.